DETERMINANTS OF INTERORGANIZATIONAL RELATIONSHIPS IN SCIENCE AND TECHNOLOGY PARKS: THEORETICAL AND EMPIRICAL EVIDENCE (Gestão & Regionalidade, 2015)
The study aims to identify the factors that determine the formation of interorganizational relationships in the context of science and technology parks. To conduct the study, which consists of qualitative research with multiple case studies, we selected two parks: one located in Brazil and the other in Portugal. The survey's main findings are represented by the theoretical and empirical evidence found in the context of science and technology parks, and the need for reciprocity and legitimacy proved critical to the formation of interorganizational relationships. Although these determinants match the primary theoretical and empirical evidence, other elements may influence the relationship, such as cultural aspects, environmental uncertainty, risk aversion and mistrust.